2005
DOI: 10.3758/bf03196051
|View full text |Cite
|
Sign up to set email alerts
|

Two-itemsame-different concept learning in pigeons

Abstract: We report the first successful demonstration of a simultaneous, two-item same-different (S/D) discrimination by 6 pigeons, in which nonpictorial color and shape stimuli were used. This study was conducted because the majority of recently successful demonstrations of S/D discrimination in pigeons have employed displays with more than two items. Two pairs of stimulus items were simultaneously presented on a touch screen equipped computer monitor. Pigeons were reinforced for consistently pecking at either the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 43 publications
5
81
1
Order By: Relevance
“…When we developed our procedure for pigeons and first presented our findings at the International Conference on Comparative Cognition in 2001, only one published study had found evidence that pigeons could learn an abstract S/D concept with two-item displays to any high degree of accuracy (72%; . Since that time other articles have been published showing some support for twoitem S/D concept learning in pigeons (Blaisdell & Cook, 2005;Cook, Kelly, & Katz, 2003). Like the study both of these studies found partial transfer.…”
Section: Importance Of Two-item Same/different Discriminationsupporting
confidence: 64%
See 1 more Smart Citation
“…When we developed our procedure for pigeons and first presented our findings at the International Conference on Comparative Cognition in 2001, only one published study had found evidence that pigeons could learn an abstract S/D concept with two-item displays to any high degree of accuracy (72%; . Since that time other articles have been published showing some support for twoitem S/D concept learning in pigeons (Blaisdell & Cook, 2005;Cook, Kelly, & Katz, 2003). Like the study both of these studies found partial transfer.…”
Section: Importance Of Two-item Same/different Discriminationsupporting
confidence: 64%
“…Partial transfer, as opposed to full transfer, is suggestive and encouraging but is inconclusive due to the possibility that multiple cues are controlling behavior (criterion 3). The interpretation of the results from Blaisdell & Cook (2005) is further complicated by retesting transfer with the same stimuli (without statistical support to rule out learning of the transfer stimuli, criterion 2), questionable novelty of some colors tested during transfer (criterion 1), and the use of two stimulus pairs presented simultaneously (i.e., 4 stimuli) in the procedure. This latter complication may be on a slightly different level, provided the pigeons were doing what people would do if they were instructed to "choose the pair with two different stimuli."…”
Section: Importance Of Two-item Same/different Discriminationmentioning
confidence: 99%
“…In recent years, studies of both birds and mammals have revealed even better evidence for the transfer of conceptual same/different discriminations (e.g., Blaisdell & Cook, 2005;Katz, Wright, & Bachevalier, 2002;Mercado, Killebrew, Pack, Macha, & Herman, 2000;Oden, Thompson & Premack, 1988;Pepperberg, 1987;Wright, Cook, Rivera, Sands, & Delius, 1988;see Wasserman, Young, &Cook, 2004 and for reviews). These more recent experiments have shown that experience with several examples of same/different relations increases the tendency of pigeons and both old-and new-world monkeys to transfer that training to new stimuli (Katz, Wright, & Bachevalier, 2002;Wright et al, 1988;Wright, Rivera, Katz & Bachevalier, 2003).…”
Section: Same/different Learningmentioning
confidence: 99%
“…For example, Blaisdell and Cook (2005) found that different pigeons taught to peck at a pair of different items, but not to peck at a pair of same items, learned faster than same pigeons trained to peck at a pair of same items, but not to peck at a pair of different items. Similarly, Castro, Kennedy, and Wasserman (2010) taught a single group of pigeons to peck at a same array or a different array of items depending on a superordinate color cue; the birds learned to peck "different" more quickly than they learned to peck "same."…”
mentioning
confidence: 99%